SciVee 2012
DOI: 10.4016/46316.01
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Hemoglobin Disorders, Infection, and Deficiencies of Iron and Vitamin A Determine Anemia in Young Cambodian Children

Abstract: In Cambodia, many factors may complicate the detection of iron deficiency. In a cross-sectional survey, we assessed the role of genetic hemoglobin (Hb) disorders, iron deficiency, vitamin A deficiency, infections, and other factors on Hb in young Cambodian children. Data on sociodemographic status, morbidity, and growth were collected from children (n = 3124) aged 6 to 59 mo selected from 3 rural provinces and Phnom Penh municipality. Blood samples were collected (n = 2695) for complete blood count, Hb type (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…Many Egyptians have developed the concept of drinking tea right after eating. Tea is very healthy, however, some studies have shown that tea interfere with the absorption of iron [30] in our work about two third of the children consume tea immediately after meals 3times and more and the consumption increasing with age this was similar to [20,31].…”
Section: Discussionsupporting
confidence: 78%
“…Many Egyptians have developed the concept of drinking tea right after eating. Tea is very healthy, however, some studies have shown that tea interfere with the absorption of iron [30] in our work about two third of the children consume tea immediately after meals 3times and more and the consumption increasing with age this was similar to [20,31].…”
Section: Discussionsupporting
confidence: 78%
“…To account for the elevation of ferritin in the presence of inflammation, Thurnham et al (23) have developed correction factors (CFs) based on the stages of inflammation (incubation and early and late convalescence) with the use of data from 32 studies of apparently healthy individuals in the absence of overt disease in over 10 countries. The accuracy of these CFs has not yet been studied in populations with a high prevalence of hemoglobin (Hb) disorders, some of which are known to increase ferritin and sTfR concentrations (e.g., homozygous Hb EE) (12,25). Hb disorders are autosomal recessive and can be inherited in the homozygous or the heterozygous form (also referred to as a ''trait'') (26).…”
Section: Introductionmentioning
confidence: 99%
“…In Cambodia, genetic Hb disorders affect~50% of the population, the most prevalent of which are Hb E variants and alpha-thalassemia [31][32][33]. Hb E variants, in particular, result in an altered structure of the beta globin chain of Hb resulting in an unstable Hb molecule [34][35][36], hence the commonly used term 'structural variants'.…”
Section: Introductionmentioning
confidence: 99%